Islam's Classical Period: Examining the Great Contribution of the Khulafahur Rashidin - Mulyani, Ani; Tabroni, Imam; Agustina, Tri Nur Utami; Wei, Zhang; Xu, Shanshan (International Journal of Educational Narratives, 2023)
Background. History is a very important reference for building the future. Through it, we can know what and how Islam developed in the past. Purpose. However, sometimes we as Muslims have not been able to see history comprehensively. So we tend to walk aimlessly and repeat the mistakes of the past. Method. The study involved 288 university students from Chinese, Japanese, and Korean TFL settings, and the data from questionnaires were analysed using appropriate statistical methods. Results. This is where the discussion of history serves as a reflection that in the past there has been a story that we should learn to design and plan well for a brilliant future without being shaken by any force. Conclusion. The development of Islam during the time of the Prophet Muhammad and his companions was a period of Islam in the era of glory, it can be seen how the purity of Islam itself with the existence of the main actors and factors, namely the Prophet Muhammad.